Preparation and characterization of nanoparticles from quaternized cyclodextrin-grafted chitosan associated with hyaluronic acid for cosmetics - Sakhiran Sakulwech; Nattaya Lourith; Uracha Ruktanonchai; Mayuree Kanlayavattanakul (Elsevier, 2018)
Hyaluronic acid (HA, 20-50 kDa) is a hydrophilic macromolecule   Peer review under responsibility of Shenyang Pharmaceutical University. with anti-wrinkle effects and moisturizing properties. However, its high molecular weight prevents it from penetrating into the deeper layers of the skin and, thus, limits its benefits to topical effects. Thus, the objective of this study is to prepare nanoparticles of quaternized cyclodextrin-grafted chitosan (QCD-g-CS) associated with HA in different molar ratios of QCD-g-CS and HA. The conjugation of the carboxylic moieties of HA and the amides of QCD-g-CS was confirmed by Fourier-transform infrared spectroscopy. Thus, the system was optimized to create nanoparticles with a small size (235.63 ± 21.89 nm), narrow polydispersity index (0.13 ± 0.02), and zeta potential of 16.07 ± 0.65 mV. The association efficiency and loading efficiency were determined by ultra-performance liquid chromatography as 86.77 ± 0.69% and 10.85 ± 0.09%, respectively. The spherical morphology of the obtained nanoparticles was confirmed by transmission electron microscopy. Moreover, the in-vitro hydrating ability was significantly higher (P < 0.001) than that of bulk HA (3.29 ± 0.41 and 1.71 ± 0.05 g water/g sample, respectively). The safety of these nanoparticles at concentrations in the range of 0.01-0.10 mg/ml was confirmed via tests on human skin fibroblasts. Together, these results demonstrate that the developed nanoparticles are promising for future applications in cosmetics. Keywords: Hyaluronic acid, QCD-g-CS, Polymeric nanoparticles, Ionic gelation, Delivery system